Этнические проблемы истории Центральной Азии в древности (II тысячелетие до н.э.) - Miroshnikov, L. I.; Litvinsky, B. A.; Asimov, M. S. (1981)
Ethnic Problems of the History of Central Asia in the Early Period (Second Millennium B.C.); Proceedings of the International Symposium on Ethnic Problems of the Ancient History of Central Asia, Second Millennium B.C., Dushanbe, October 17-22, 1977.